A Study on the Influence of Emotional Intelligence on Academic Satisfaction Among Chinese College Students: The Mediating Effect of Learning Engagement and the Moderating Effect of Social Support - Wang, Yan; Yang, SeYoung (Journal of Educational Research and Policies, 2024)
This study primarily examines the interconnections among college students' Emotional Intelligence, Learning Engagement, Academic Satisfaction, and Social Support. A total of 535 college students participated in the survey utilizing the Emotional Intelligence Scale (EIS), the Learning Engagement Scale (UWES-S), the Perceived Social Support Scale (PSSS), and the University Version of Learning Satisfaction Scale. Findings indicate that the Emotional Intelligence of college students exhibits significant variability, with notable gender disparities. Emotional Intelligence is found to have a substantial positive influence on both Academic Satisfaction and Learning Engagement, while Learning Engagement further positively affects Academic Satisfaction. Additionally, Learning Engagement serves as a mediating factor between Emotional Intelligence and Academic Satisfaction, and Social Support acts as a moderating variable in the Emotional Intelligence-Academic Satisfaction dynamic.